2019
DOI: 10.1101/654624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of thermal extremes on coral reef fish behaviour in the Persian Gulf

Abstract: Despite increasing environmental variability within marine ecosystems, little is known about how coral reef fish species will cope with future climate scenarios. The Arabian/Persian Gulf is an extreme environment, providing an opportunity to study fish behaviour on reefs with seasonal temperature ranges which include both values above the mortality threshold of Indo-Pacific reef fish, and values below the optimum temperature for growth. Summer temperatures in the Gulf are comparable to those predicted for the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Using a combination of field observations and aquaria experiments, D'Agostino et al (2019) showed that during the metabolically challenging summer and winter seasons, the damselfish Pomacentrus trichrourous substantially reduced their feeding rates and movement, but increased feeding and activity during the shoulder seasons when conditions are most benign, presumably to maximize energy intake when physiological demands were more optimal. Individuals also switched diets in a manner that suggest behavioral modification to maximize energy budgets, feeding mainly on plankton in the cooler seasons, but on a combination of plankton and a variety of benthic resources during the hottest time of year when energetic demands would be greatest (D'Agostino et al 2019). Together, these studies suggest that adopting a more flexible behavioral and dietary lifestyle may be necessary to support the physiological and energetic demands presented in thermally extreme seas.…”
Section: Thermally Extreme Seasmentioning
confidence: 99%
“…Using a combination of field observations and aquaria experiments, D'Agostino et al (2019) showed that during the metabolically challenging summer and winter seasons, the damselfish Pomacentrus trichrourous substantially reduced their feeding rates and movement, but increased feeding and activity during the shoulder seasons when conditions are most benign, presumably to maximize energy intake when physiological demands were more optimal. Individuals also switched diets in a manner that suggest behavioral modification to maximize energy budgets, feeding mainly on plankton in the cooler seasons, but on a combination of plankton and a variety of benthic resources during the hottest time of year when energetic demands would be greatest (D'Agostino et al 2019). Together, these studies suggest that adopting a more flexible behavioral and dietary lifestyle may be necessary to support the physiological and energetic demands presented in thermally extreme seas.…”
Section: Thermally Extreme Seasmentioning
confidence: 99%
“…faster juvenile growth but earlier asymptotic growth for fish living in warmer environments) (Trip et al 2014), suggesting that salinity and perhaps even productivity are exhibiting a strong influence on differences in growth between regions. Interestingly, growth rates of populations within the Oman Sea, where salinity conditions are predominantly stable, were impacted more strongly by salinity fluctuations compared to populations within the Arabian Gulf, suggesting Arabian Gulf's populations may have higher capability of acclimation to seasonal and interannual changes in environmental conditions (Rummer and Munday 2017;D'Agostino et al 2019). While numerous studies have examined the implications of increasing temperature and temperature variability on coral reef fish growth (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The pale-tail damselfish (Pomacentrus trichrourus) appears able to mitigate bioenergetic inefficiency associated with the fluctuating and extreme water temperature within the Arabian Gulf by downregulating costly activities during winter and summer, while upregulating activity and increasing energy stores in spring (D'Agostino et al 2019). In this respect, P. trichrourus, P. maculosus and Pomacentrus aquilis all show a degree of feeding plasticity in the Arabian Gulf (Shraim et al 2017;D'Agostino et al 2019), suggesting that such plasticity in feeding may be an important factor in understanding growth rate and overall body size of all three species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations